Music industry and the determinants of cultural consumption in live music in Colombia; La industria musical y los determinantes del consumo cultural en la música en vivo en Colombia - Doris Lilia Andrade Agudelo; Liseth Yulieth Idrobo Sulbaran; Víctor Manuel Galindo Sánchez (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2022)
– In recent decades, a growing interest in the micro and meso economic foundations of competitiveness has emerged worldwide. Many authors have seek to explain this phenomenon using approaches that rely on endogenous and relational capabilities of firms. Relational capabilities are exercised in contact with other agents and allow knowledge that circulate among networks to be properly exploited. This paper analyzes this type of entrepreneurial skills and the links that exist between software companies in the city of Bahía Blanca. The method used to study this phenomenon is social network analysis or SNA.
Keywords: C25; L82; G38; 330; music industry; cultural industry; cultural consumption